Education for Prevention of Alcohol and Tobacco Consumption in Secondary Education in Cubal - Adelino Pena Calei; Augusto José Fazenda (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The objective of the study was to characterize the current situation of alcohol and tobacco consumption in secondary school, with a view to the health education, in Cubal, Benguela province, Angola. The study was carried out in the first and second trimester of the school year and the survey to the teacher and student, interviews with school principals and participant`s observation during class and in the playground were used as methods. The sample was taken from the Fist Cycle of Secondary Education at "Kilamba" School and it concluded that teachers and students presented themselves to classes after comsuming alcohol and used to consume tobacco during break time in the court-yard. Although teachers and students were aware of the negative effect of alcohol and tobacco consumption, it was noticed that the problem at issue was not systematically addressed in the teaching-learning process of Geography, which would contribute to the prevention of alcohol and tobacco consumption in school and in general life of the citizen.